Gold-catalysed functionalisations of yndiamides - Tong, Z (2023)
Yndiamides, doubly nitrogen-substituted alkynes, could serve as versatile precursors to various 1,2-diaminated products. This thesis focused on the gold-catalysed functionalisations of yndiamides via the generation of gold carbenes. During the course of this study, three projects have been completed: 1. Gold-catalysed oxidative functionalisation of yndiamides with pyridine N-oxides to synthesise unnatural amino acid derivatives. Regioselectivity was achieved by introducing minor steric bias between the two nitrogen substituents. 2. Gold-catalysed cyclisation between yndiamides and isoxazoles to form highly substituted 2,3-diaminopyrroles. The reaction outcome could be switched to formal [5+2] cyclisation by using benzisoxazoles. Regioselectivity was also achieved by using sterically-biased non-symmetric yndiamides. 3. Computational investigation into the regioselectivity of the gold-catalysed cyclisation between yndiamides and isoxazoles. DFT calculation revealed a Curtin-Hammett scenario for isoxazole addition as the key to the regioselectivity. Besides the three projects above, a brief exploration of tetrazolo[1,5-a]pyridines as novel nitrene transfer reagents is also presented.